Analisis Strategi Pemasaran Sayuran Hiroponik di Tengah Pandemi Covid-19 - Ardi, Fiza; Prihtanti, Tinjung Mary (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 10 No 1 (2022): Jurnal Manajemen AgribisnisDO - 10.24843/JMA.2022.v10.i01.p09, 2022)
The purpose of this study was to analyze the vegetable marketing strategy implemented by Bale Hydroponics Salatiga in the midst of the Covid-19 pandemic. This research was conducted at Bale Hydroponics Jalan Mutiara No. 35 Bugel Village, Sidorejo District, Salatiga City - 50714, Central Java – Indonesia in June 2020 - August 2020. The study used descriptive qualitative methods. Collecting data using observation, interviews, and documentation studies. The data used include primary data and secondary data, the data obtained will be analyzed using SWOT and QSPM analysis. The results showed that the vegetable marketing strategy implemented by Bale Hydroponics Salatiga in the midst of the Covid-19 pandemic was the strategy that received the highest STAS score, namely collaborating with potential distributors to increase market share. In addition to these strategies, there are alternative strategies that are recommended to Bale Hydroponics such as public education, improving vegetable quality, adding vegetable variants, adding farmer partners and cultivation areas, increasing promotions, using the latest equipment, and opening branches outside Salatiga.